Progress in Sputter Growth of β‐Ga2O3 by Applying Pulsed‐Mode Operation. Issue 10 (20th April 2020) - Schurig, Philipp; Michel, Fabian; Beyer, Andreas; Volz, Kerstin; Becker, Martin; Polity, Angelika; Klar, Peter J.
Abstract : β ‐Ga2 O3 thin films are deposited by pulsed radio‐frequency (RF) magnetron sputtering on c‐sapphire substrates, using a stoichiometric Ga2 O3 target and a constant gas flux of an argon–oxygen mixture. Pulsed sputtering offers a way to overcome the restrictions of conventional sputtering. The parameters RF power and pulse duty cycle (PDC) are varied systematically to optimize the synthesis of Ga2 O3 thin films. Subsequently, the resulting as‐deposited (AD) Ga2 O3 layers are analyzed in terms of structural and optical properties and the results are compared with those on the samples treated by postdeposition rapid thermal annealing. Based on this analysis, the process parameters are evaluated in terms of β ‐Ga2 O3 formation. Postdeposition temperature treatments are found to yield a better crystal quality. However, a strong interdiffusion with the Al2 O3 substrate is observed. The optical bandgap of the sputtered thin films is found to be quite independent of the RF sputtering power but to depend strongly on the PDC used, whereas the layer thickness rather strongly increases with both of those growth parameters. These evolutions are assigned to changes in the energy and ionic species of the plasma. Traces of GaOx ‐related phases in addition to β ‐Ga2 O3 are found in the interphase between the growing thin films and the underlying substrate. Abstract : Beta‐Ga2 O3 thin films are deposited by pulsed radio‐frequency (RF) magnetron sputtering, varying RF power and pulse duty cycle (PDC). The resulting layers are analyzed in terms of structural and optical properties and the results are compared with effects of rapid thermal annealing. The optical bandgap of the sputtered thin films depends strongly on the PDC used.